Pengaruh Terapi Dzikir Terhadap Kecemasan Kematian Pada Lansia di Panti Perlindungan Rehabilitasi Sosial Lanjut Usia Budi Sejahtera - Nor Afipah, Rika; Lisnawati, Ica; Afni Oktavia, Nor (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
The elderly are a vulnerable group that easily experiences anxiety about death due to a decline in physical, psychological, and social functions. This anxiety negatively impacts spiritual well-being and overall quality of life. Dhikr therapy, which is a spiritual practice of repeatedly remembering Allah SWT, is believed to provide inner peace and reduce psychological pressure. This study aims to analysis the effect of dhikr therapy on death anxiety in the elderly residing at the Budi Sejahtera Social Rehabilitation. This study uses a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 85 elderly individuals divided into intervention and control groups using purposive sampling technique. The intervention group was given dhikr therapy for three consecutive days, each session lasting 15 minutes. The instrument used was the Death Anxiety Scale (DAS). The results of the Wilcoxon Signed Rank Test showed a significant reduction in anxiety (p = 0.000), with the average score decreasing from 45.8 to 32.6. The Mann-Whitney test indicated a significant difference between groups (p = 0.004). This study uses a simple, inexpensive, and easily applicable culturally-based spiritual approach. Dhikr therapy is recommended as a spiritual nursing intervention to improve emotional well-being and acceptance of end-of-life among the elderly